A simulator of mechanisms of acute control of human hemodynamics - Grygoryan, R.D.; Degoda, A.G.; Kharsun, V.S.; Dzhurinsky, E.A. (Інститут програмних систем НАН України, 2019)
A software simulator (SS) of the physiological mechanisms that provide the acute control of human hemodynamics is created. SS is based on a mathematical model (MM) describing reflexes, the source of information in which are mechanoreceptors located in the right ventricle of the heart, in the aortic arch and in the carotid sinuses. A previously developed model of an uncontrollable cardiovascular system with a pulsating heart is used as an object of control (OC). In MM, the duration of the cardiac cycle, the rigidity and the unstressed volume of the vascular areas of the body are the target of regulatory actions. MM and OC are realized in C++. Oriented to the physiologist, the interface provides him / her with the ability to turn on / off any of the reflexes, to conduct test studies (including imitation of dosed blood loss or blood transfusion). SS is still functions autonomously. Subsequently, after modeling also endocrine physiological mechanisms of long-term effects on hemodynamics, SS will become a virtual tool for research of complex mechanisms that optimize human hemodynamics.Problems in programming 2019; 1: 90-98